The collection of antiquarian information for the early Ordnance Survey maps of Scotland - Davidson, J L (Proceedings of the Society of Antiquaries of Scotland, 1987)
This paper pays tribute to a little recognized body of amateur archaeologists who in the 19th century compiled a nation-wide Record of archaeological and historical sites in the British Isles. Scotland is fortunate that this ecord still exists, as the English and Welsh Name Books were destroyed during an air raid on Ordnance Survey headquarters at Southampton in 1940. The appearance of antiquities on the first-edition Ordnance Survey maps has been taken for granted by researchers for decades, but the background account of why and how antiquities were recorded is probably little appreciated. This paper explains the role of the Ordnance Survey in Scotland during the last century in forming this Record, the involvement of this Society, the reasons why antiquities were published on the maps and described in the Name Books, the controversies some descriptions inadvertently raised, and the format of the Books themselves.